Studi Anatomi Catecholamine Mesolimbic Pathway pada Kalong Kapauk (Pteropus vampyrus) Asal Pulau Timor - Filphin Adolfin Amalo; Tri Wahyu Pangestiningsih; Dwi Liliek Kusindarta (JURNAL KAJIAN VETERINER, 2019)
Catecholamine mesolimbic pathway (CMP) is a dopamine pathways of the brain that derived from cell bodies in the ventral tegmental area (VTA) to the limbic area i.e. nucleus accumbens, amygdala and hippocampus. In normal conditions, CMP plays a role as controls of motor activity, motivation, emotional and cognitive. Bats are flying mammals which can be potential as natural reservoir of rabies. One of the symptoms of animal rabies is impaired in emotional control that related with limbic system. Kalong kapauk (Pteropus vampyrus) is one of the species of bats that distributed in south Sumatra, Java, Borneo, and spread out to the island of Timor, East Nusa Tenggara. The aim of this research is studying the anatomical structures in CMP of kalong kapauk (Pteropus vampyrus) from Timor island. Four kalong kapauk (Pteropus vampyrus) from Soe-Timor island, East Nusa Tenggara was anaesthetized by using ketamine (20 mg/kg bw) and xylazin (2 mg/kg bw). In deep anesthesia condition, animals were perfused by using physiological saline and after the blood were removed well, the physiological saline were changed to 10% buffered formalin as a fixative. The brain were removed from the cranium, dissected midsagital and processed for histology by paraffin method. The brains were cut in 12 μm thickness and then it stained by using cresyl echt violet and immunohistochemistry by tyrosine hydroxilase antibody. The sections were examined for shape and size of neurons in the VTA and their axonal pathways by light microscope and were documented using a digital camera. The results were analyzed descriptively. The results shows that neurons in the VTA are bipolar and multipolar in shape with the size of 10-32 μm (mean 20.31 ± 4.40 μm) and densities are 15.33 ± 5.71 cells/0,116 mm2. The area of nucleus accumbens, amygdala, and cornua ammonis 3 of hippocampal are TH immunoreactive as the axon terminal. The conclusion of this study is there are catecholaminergic neurons in the VTA that made an area limbic pathways i.e. nucleus accumbens, amygdala, and cornua ammonis 3 of hippocampal.